Controllability of nonlinear stochastic fractional systems with distributed delays in control. Issue 3 (3rd July 2017) - Mabel Lizzy, R.; Balachandran, K.; Suvinthra, M.
Abstract : In this paper we study the controllability of linear and nonlinear stochastic fractional systems with bounded operator having distributed delay in control. The necessary and sufficient conditions for controllability of the linear system is obtained. Also, the nonlinear system is shown controllable under the assumption that the corresponding linear system is controllable and using the Banach contraction principle.